Evaluation of MRI in the diagnostic accuracy of extrahepatic metastases in neuroendocrine tumors in comparison with the reference standard somatostatin-receptor–PET/CT - Ingenerf, Maria; Rübenthaler, Johannes; Wenter, Vera; Zacherl, Mathias; Völter, Friederike; Winkelmann, Michael; Karim, Homeira; Schinner, Regina; Ricke, Jens; Berger, Frank; Schmid-Tannwald, Christine (Frontiers in Oncology, 2023)
Purpose: The aim of this study was to compare the diagnostic performance of different sets of MR sequences in detecting extrahepatic disease of NETs on routine liver MRI.Method: 127 patients with NETs with and without hepatic and extrahepatic metastases who underwent liver MRI and SSTR-PET/CT were retrospectively analyzed. Two radiologists evaluated in consensus in four sessions (1.non-contrast T1w+T2w (NC), 2. NC+DWI, 3. NC+ contrastenhanced T1w (CE), 4. NC+DWI+CE) the presence and number of metastases (lymph nodes, bone, peritoneal surface, lung base and abdominal organ). Sensitivity, specificity, positive and negative predictive value for detection of metastases were calculated for each session in a patient-based manner; detection and error rates were calculated for lesion-based analysis. Comparison between the MR-sessions and PET/CT was performed with the McNemar test. This is a provisional file, not the final typeset article Results: Regarding all 1094 lesions detected in PET/CT, NC+DWI and NC,CE+DWI identified most true-positive lesions 779 (71%) and 775 (71%), respectively). Patient-based analysis revealed significantly higher sensitivity by NC+DWI (85%) than NC and NC+CE (p=0.011 and 0.004, respectively); the highest specificity was reached by NC+CE+DWI (100%). Site-based analysis revealed highest detection rates for lymph node metastases for NC+DWI and NC, CE+DWI (73% and 76%, respectively); error rates were lower for NC,CE+DWI with 5% compared to 17% (NC+DWI). Detection rates for bone metastases were similarly high in NC+DWI and NC,CE+DWI (75% and 74% respectively), while CE showed no benefit. For peritoneal metastases highest sensitivity was reached by NC+DWI (67%).Conclusions: The combination of NC+DWI showed better sensitivities than the combination of NC+CE. NC+DWI showed similar, sometimes even better sensitivities than NC+CE+DWI, but with lower specificities.